PENYIDIKAN TERHADAP KASUS PERCOBAAN MELAKUKAN TINDAK PIDANA DI WILAYAH HUKUM KEPOLISIAN RESOR ROKAN HULU - Siska Amelya; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal action is prohibited by a rule of law that is accompanied by threats (sanctions) in the form of spesific criminal against those who violate.a ban was intended to act where a situation or incident caused by the behavior itself. Whereas criminal threats addressed to the people who bring it.of the above cases has taken law enforcement.a precess that has been done is the investigation by the police resort Rokan Hulu. But, unfortunately the process of invistigations conducted by the police did not run smoothly because there are many problems and issues found in field.This research is a sociological law.whereas seen from the desciptive nature of this study, the research provides a clear and detailed picture of the problems studied by authors, namely the role of the police investigations criminal resort Rokan Hulu towards the investigations of criminal trial (poging). Everyone who suffered, saw, witnessed and or become victims of the events that constitute a criminal offense has the right to file a police report or complaint to both oral and written. As well as for people who know a conspiracy to commit a crime, immediately the order to report to the police. Then civil servants in order to carry out their duties knowing about the events that constitute a criminal offense shall immediately report it to the police.When conducting the investigations of criminal cases experiments conducted by the police of conducting enforment investigations, prosection, arrest, detenion, searches, seizure, examination of suspects and witnesses. Barriers that occur when performing investigations poging criminal casses such as: personnel where the lack of part of the investigation, where the quality of human resources in order to have high quality in the task as law enforcement officers, minimal infrastructure and aquipment during processing the scene is not as complete as that owned by police. Efforts made to overcome obstacles in the investigation is to conduct socialization, being open, coaching members of an adequate education and supporting infrastructure that supports.Key words: investigation, police, crime, arrest, poging.